Pemanfaatan Pojok Baca dalam Menumbuhkan Minat Belajar dan Membaca Siswa SDN Pakis V Surabaya - Fadilah, Lailatul; Yuliana, Leni; Bahtiar, Reza Syehma (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to explore the strategies for utilizing reading corners to increase the reading interest of elementary school students. The low reading interest in Indonesia, which ranks 60th out of 61 countries, serves as an important backdrop for this research. The research method uses a qualitative approach with a case study design conducted in class IV C of SDN Pakis V Surabaya. Data collection techniques include in-depth interviews, participatory observation, and documentation involving the research subjects, which are the teachers and students of class IV C. Data analysis uses an interactive model through data reduction, data presentation, and conclusion drawing. The research results show that the reading corner has been utilized well by students with a visiting frequency of 2-3 times a day for 15-20 minutes. The reading corner has a significant positive impact on students' interest in learning and reading, marked by changes in reading habits that are more independent, an increase in public speaking skills, a broadening of knowledge, improvement in academic grades, and achievements in literacy competitions. Supporting factors for success include the support of the principal, the active role of teachers, parental support, the availability of 65 books with various types, and the effectiveness of the 15-minute reading program. However, there are inhibiting factors such as limited space, lack of updates to the book collection, the absence of comfortable seating facilities, and uneven student interest in reading.